The value of Stilbestrol in beef cattle rations. - Richardson, D.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Twenty-seven Hereford steer calves were divided as equally as possible into three lots of 9 animals each. One lot received stilbestrol at the rate of 6 milligrams per head daily for the first 56 days. The rate was increased to 10 milligrams per head daily for the remainder of the test. Previous work indicated a lower level for young calves might be more desirable during the first part of the feeding period. The other two lots served as controls. Due to lack of pen 'space, they were fed together. All animals will graze bromegrass pasture without stilbestrol this summer. After returning to the feed lot, all animals accept one control lot will receive stilbestrol in the fattening ration.
Keywords: Beef; Stilbestrol; Gain; Feed efficiency